Successive phase transitions in the orthovanadate TmVO3. (5th August 2015) - Sarkar, Tapati; Ivanov, Sergey A; Bazuev, G V; Nordblad, Per; Mathieu, Roland
Abstract: Synthesis and crystal structure, magnetization and heat capacity measurements of phase pure polycrystalline TmVO3 are reported. TmVO3 was stabilized in the orthorhombic structure by thermal treatment of the precursor TmVO4 in a reducing atmosphere. Magnetization and heat capacity measurements reveal the presence of several successive structural and magnetic phase transitions in this compound. At T = 108 K, the sample undergoes a transition from a paramagnetic state to an antiferromagnetic state, followed by a second transition at 78 K which is related to spin and orbital reorientation. The heat capacity measurements reveal the presence of a third transition in the paramagnetic state (at T = 175 K), which corresponds to a structural phase transition and orbital ordering. At low temperatures (~15 K) and weak fields, there is an anomaly in the magnetization, which may be associated with antiferromagnetic short range ordering of the Tm 3+ ions.